Water quality monitoring in Selangor river basin / Hamizat Othman - Othman, Hamizat (1998)
This case study of Selangor River Basin, consisting of reviewing, studying and comparing the adequacy of existing monitoring network which the following hypothesis is tested in the work ; 'The existing Control Standard (Effluent Limit) is not adequate to control water pollution' . This thesis also performed the mass balance analysis to the present system and compare to the proposed system in order to study the impact of pollution from palm oil and rubber processing factories on Selangor River Basin. From the analysis done, shows that the above mentioned factories are not the major pollutant contributor to the study area . The results conclude that there is not enough evidence to say that the existing control standard (effluent limit) is not adequate to control water pollution although some of certain aspect needs slight adjustment.